Different diagnoses, similar experiences : narratives of mental health, addiction recovery and dual diagnosis - Norton, Michael John; Cullen, Oliver John (Emerald Publishing Limited, 2024)
Emerging from an era of changing mental health and addiction services, Different Diagnoses, Similar Experiences is the first work in its field to gather narratives of mental health, addiction and dual diagnoses into one publication, as well as to critically examine the differences and similarities of these experiences. Documenting their own personal narratives, contributors share their unique journey to recovery, while Michael John Norton and Oliver John Cullen construct a series of recommendations for those working within similar circumstances to understand and embrace both the individuality and the shared experience of the recovery process. Giving voice to those in recovery who have chosen to channel their real-life experiences for the sake of helping others, this timely work offers valuable insights for researchers, mental health professionals, family members and support networks, as well as anyone whose life has been touched by the shadows of mental illness, addiction or dual diagnosis.